The relationship between financial leverage, liquidity, cash flow and net fixed asset toward investment: evidence from Bursa Malaysia / Richie Sidi - Sidi, Richie (2017)
The purpose of this paper had been conducted by the study is to identify the relationship between financial leverage, liquidity, cash flow and net fixed asset toward investment of listed companies in Bursa Malaysia. From that, the study collects the data collection period from 2010 until 2015. For the finding of this research, the study can identify that cash flows and net fixed asset are the variables give a positive significant relationship toward investment decision. Additional, we can saw from correlation coefficient result that both of the variables have a good effect toward investment decisions and always influence the independent variable in every single changes in investment. However, the study also identifies that financial leverage and liquidity build a negative significant relationship toward the investment, and both of this variable had failed to reject H null. For overall, the final result of this study had shown that a positive significant relationship financial leverage and investment decision. Practical implications of this study are to identify the relationship between financial leverage and investment decisions by referred to the listed companies in Bursa Malaysia. For this line of the future researcher, they need to take serious about the several unique of Malaysia market by analyzing something different such as comparing listed companies in Malaysia with East Asian companies. This research paper is to extend and update the existing the literature review on the relationship between financial leverage and investment decision by referring to listed companies in Bursa Malaysia and extensive the data over a more recent period.